2023
DOI: 10.1007/s00125-023-05879-7
|View full text |Cite
|
Sign up to set email alerts
|

Causal factors underlying diabetes risk informed by Mendelian randomisation analysis: evidence, opportunities and challenges

Abstract: Diabetes and its complications cause a heavy disease burden globally. Identifying exposures, risk factors and molecular processes causally associated with the development of diabetes can provide important evidence bases for disease prevention and spur novel therapeutic strategies. Mendelian randomisation (MR), an epidemiological approach that uses genetic instruments to infer causal associations between an exposure and an outcome, can be leveraged to complement evidence from observational and clinical studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…The existing body of evidence linking diabetes and bacteria primarily focuses on intestinal flora. 35 Previous observational studies have revealed a higher incidence of bacterial pneumonia among hospitalized individuals with diabetes. 36 Additionally, patients with inadequate blood glucose control exhibit an elevated susceptibility to diabetes-related pneumonia necessitating hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The existing body of evidence linking diabetes and bacteria primarily focuses on intestinal flora. 35 Previous observational studies have revealed a higher incidence of bacterial pneumonia among hospitalized individuals with diabetes. 36 Additionally, patients with inadequate blood glucose control exhibit an elevated susceptibility to diabetes-related pneumonia necessitating hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the complex pathogenesis of diabetes and its tendency to be complicated by other disease complications, we believe that the association between type T2DM and vitiligo mentioned in observational studies may be related to confounding factors. Two MR Analyses(21, 22) suggested a significant causal association between T2DM and depression, and one meta-analysis(23) concluded that vitiligo induces varying degrees of psychological problems. This finding may be an important reason why vitiligo is associated with T2DM in several observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…26 The design has been widely used in medical research due to two major merits. 27,28 First, the method can minimize confounding because genetic variants are randomly assorted at conception and thus not associated with confounder (e.g., environmental and self-adopted factors). This process at the population level resembles the randomization process in the randomized controlled trials.…”
Section: Mendelian Randomization Analysismentioning
confidence: 99%